2017
DOI: 10.1158/1078-0432.ccr-16-2054
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Abiraterone Ultraresponsive Phenotype in Castration-Resistant Prostate Cancer Patient-Derived Xenografts

Abstract: Purpose To identify the molecular signature associated with abiraterone acetate (AA) response and mechanisms underlying AA resistance in castration-resistant prostate cancer patient-derived xenografts (PDXs). Experimental Design SCID mice bearing LuCaP 136CR, 77CR, 96CR, and 35CR PDXs were treated with AA. Tumor volume and prostate-specific antigen were monitored, and tumors were harvested 7 days post-treatment or at end of study for gene expression and immunohistochemical studies. Results Three phenotypic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…These results further confirm that AR interacts with BMI1, but not RING1B. More importantly, using two CRPC patient-derived xenograft (PDX) models 11 —LuCaP 35CR and 86.2CR—we further confirmed the interactions between AR and BMI1 in prostate cancer patient tissues (Fig. 1g ).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…These results further confirm that AR interacts with BMI1, but not RING1B. More importantly, using two CRPC patient-derived xenograft (PDX) models 11 —LuCaP 35CR and 86.2CR—we further confirmed the interactions between AR and BMI1 in prostate cancer patient tissues (Fig. 1g ).…”
Section: Resultssupporting
confidence: 73%
“…One of the important mechanisms of enzalutamide resistance is the increased expression of AR variants lacking the ligand-binding domain, the best characterized of which is AR-V7 6 , 7 . Using LuCaP 35CR 11 , an enzalutamide-resistant and abiraterone-resistant CRPC PDX model, we found that combinatorial treatment of PTC209 and enzalutamide significantly improves the clinical outcomes when compared with those utilizing enzalutamide alone (Fig. 6f and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 94%
“…These experiments identified consistent sensitivity to treatment with CX-5461 plus CX-6258, extending our previous work with these compounds to diverse castration-resistant tumours [11]. More broadly, our approach highlights the utility of different types of patient-derived models, including explants and PDXs, in prostate cancer research [5,3436].…”
Section: Discussionsupporting
confidence: 68%
“…The LuCaP PDX models were established from primary PCa tumors or PCa metastases derived from operative specimens and metastatic CRPC samples obtained by performing tissue acquisition necropsy at the University of Washington [20,128,129,130,131,132,133,134,135,136,137,138,139,140]. During 1991–2005, 261 PCa samples were collected from 156 patients and were implanted subcutaneously into male SCID mice.…”
Section: Patient-derived Xenograftsmentioning
confidence: 99%
“…Although abiraterone treatment significantly inhibits the proliferation of LuCaP 136CR-derived tumors, it does not inhibit or only minimally inhibits the proliferation of LuCaP 35CR-derived tumors. The molecular signature of secreted proteins associated with an abiraterone ultra-responsive phenotype has been determined [132]. The CRPC PDX models can be used to evaluate new drugs targeting histone acetyltransferase paralogue p300 and CREB-binding protein [137,138].…”
Section: Patient-derived Xenograftsmentioning
confidence: 99%